Pengaruh Persepsi Harga, Promosi, dan Kualitas Pelayanan terhadap Keputusan Pembelian Tiket Pesawat Secara Online pada Situs Tiket.com di Sumatera Barat - Nurul Amelia Putri; Syuryatman Desri; Jeri Lailatul Akbar; Sannia Reivany (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Tiket.com is an online startup founded in August 2011. This company operates an online system for ordering and purchasing tickets. Tiket.com offers a wide range of products, including hotels and hostels, plane, train and car rental tickets, as well as event and attraction tickets. Consumer purchasing decisions in online trading activities are influenced by many factors. This includes costs, promotions, sales, and services the company provides.